Changes of IgG N-Glycosylation in Thyroid Autoimmunity: The Modulatory Effect of Methimazole in Graves’ Disease and the Association With the Severity of Inflammation in Hashimoto’s Thyroiditis - Trzos, Sara; Link-Lenczowski, Paweł; Sokołowski, Grzegorz; Pocheć, Ewa (Frontiers in Immunology, 2022)
The N-glycome of immunoglobulin G (IgG), the most abundant glycoprotein in human blood, reflects pathological conditions of autoimmunity and is sensitive to medicines applied in disease therapy. The IgG structure and its effector functions are strongly dependent on the composition of N-glycans attached to the Fc fragment. Remodeling of its N-oligosaccharides can induce pathological changes that ultimately contribute to the development of autoimmunity; restoration of their physiological structure is critical to the reduction of disease symptoms. Our recently published data have shown that the pathology of autoimmune thyroid diseases (AITDs), including Hashimoto's thyroiditis (HT) and Graves' disease (GD), is accompanied by alterations of IgG N-glycans. The present study is a more in-depth investigation of IgG glycosylation in AITDs, designed to determine the relationship between the severity of thyroid inflammation and IgG N-glycan structures in HT, and to assess the impact of immunosuppressive therapy on the N-glycan profile in GD. The study material consisted of human serum samples collected from donors with elevated anti-thyroglobulin (Tg) and/or anti-thyroperoxidase (TPO) IgGs (n=68), HT patients (n=113), GD patients with up-regulated IgG against thyroid-stimulating hormone receptor (TSHR) before (n=62) and after (n=47) stabilization of TSH level as a result of methimazole therapy (study groups), and healthy donors (control group, n=90). IgG was isolated from serum using protein G affinity chromatography. N-glycans were released by PNGase F and analyzed by UPLC-MS after 2-AB labeling. UPLC-MS chromatograms were integrated into 25 peaks in the Waters UNIFI Scientific Information System, and N-glycans were assigned based on the glucose unit values and m/z ratios of the detected ions. The Kruskal-Wallis non-parametric test was used to determine the statistical significance of the results (p<0.05). The obtained results suggest that modifications of IgG sialylation and core-fucosylation are associated with the severity of HT symptoms. Methimazole therapy implemented in GD patients affected the IgG N-glycan profile; as a result, the content of bisected structures with core fucose and the sialylated oligosaccharides differed after treatment. Our results suggest that N-glycosylation of IgG undergoes dynamic changes during the intensification of thyroiditis in HT, and that in GD autoimmunity it is affected by immunosuppressive therapy.